Implementasi Agile Development Methods Dalam Perancangan Aplikasi Penjualan Berbasis E-Commerce Pada Distro Zomboy - Mad Deries Rismawan, Suhendra Anjar Dinata, Bagus Wahyu Pandhito (Jurnal Teknorama (Informatika dan Teknologi El Rahma), 2024)
In the era of rapid digital transformation, the trade industry in Southeast Asia, including Indonesia, is experiencing major changes with the increasingly widespread adoption of internet technology. In this context, distro (distribution outlets) as one of the business sectors facing pressure to adapt to the needs of consumers who are increasingly connected digitally. One relevant solution is to implement agile development methods in designing e-commerce-based sales applications. The main objective of this study is to build an effective system in managing and analyzing distro zomboy sales data in order to understand customer preferences and product availability. In addition, this study aims to create an e-commerce application that offers a personal shopping experience that suits customer preferences through the application of agile methods, especially scrum. The Research and Development (R&D) method was used in this study to develop the application. The results of the study showed that the developed system succeeded in managing and analyzing sales data effectively, so that distro zomboy could better understand customer preferences. The application of agile methods resulted in an application that was responsive and adaptive to customer needs, and contributed to increasing their satisfaction. The acceptance process and implementation system went well, supported by the active participation of stakeholders. The study concluded that agile methods provide the flexibility and quality needed to deal with rapidly changing market dynamics, enabling Zomboy Distro to improve services and achieve competitive advantage.